Non-Progressive Ataxias - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
A population-based study of 78 Swedish children with non-progressive ataxia is reported from the Department of Paediatrics, Malarsjukhuset, Eskilstuna; Department of Neuroradiology, Karolinska Institute, Stockholm; and Department of Paediatrics, University of Goteborg, Sweden.